Plasma inflammation-related proteins associated with anxiety and depression disorders in IBD patients - Min Si Zhou; Wan Ru Zhang; Yan Dang; Fang Xu; Chen Yue Xu; Zhan Wang; Chun Sai Er Wang; Si Ying Zhu; Peng Li; Jing Wu; Hai Yun Shi (Scientific Reports)
Abstract Up to 25-35% of patients with inflammatory bowel disease (IBD) suffer from anxiety or depression. Mood disorders are correlated with activated inflammatory response. However, changes of inflammation-related proteins in IBD patients with anxiety or depression disorders are still unclear. We aimed to depict the plasma proteomics characteristics of IBD patients with anxiety or depression. Adult patients diagnosed with IBD were prospectively enrolled, and the clinical data were obtained. The Hospital Anxiety and Depression Scale (HADS) was used to assess anxiety or depression levels. OLINK panel (Target 96 Inflammation) was used to quantify the plasma levels of inflammation-related proteins. Among the involved 142 IBD patients (median age 39.5, 42.96% female), 41 were comorbid with anxiety or depression symptoms. The levels of anxiety and depression symptoms in active phase group were significantly higher than those in quiescent group (P = 0.020). The anxiety and depression levels of IBD patients were positively correlated with fatigue levels (r = 0.713, P < 0.001), and negatively correlated with sleep quality (r = 0.499, P < 0.001) and quality of life (r =-0.692, P < 0.001). Plasma levels of 92 inflammation-related proteins were measured in 61 IBD patients. Up-regulated levels of fibroblast growth factor 23 (FGF-23) were found in IBD patients with anxiety or depression disorders, with an area under the curve (AUC) of 0.67(95%CI:0.53–0.81, P = 0.031). The plasma levels of C-C motif chemokine 20 (CCL20) and C-X-C motif chemokine 1 (CXCL1) were up-regulated in IBD patients with anxiety or depression, respectively, and the corresponding AUCs were 0.68 (95%CI:0.54–0.82, P = 0.036) and 0.70(95%CI:0.56–0.84, P = 0.017). Correlation analysis showed that the levels of anxiety and depression symptoms in IBD patients were negatively correlated with plasma Delta/Notch-like epidermal growth factor-related receptor (DNER) (r=-0.253, P = 0.047) and interleukin-8 (IL-8) (r=-0.275, P = 0.031) levels, and were positively correlated with the plasma levels of CXCL1 (r = 0.290, P = 0.022) and FGF-23 (r = 0.290, P = 0.022). In addition, negative correlation was found between plasma DNER levels and Mayo clinical scores in ulcerative colitis (UC) patients (r=-0.464, P = 0.001). Mood disorders are closely related to disease flare of IBD patients. The increasing levels of anxiety and depression in IBD patients are accompanied by graver fatigue, worse sleep quality and lower quality of life. Inflammation-related immune regulation is associated with the development of emotional disorders in IBD patients.